2006
DOI: 10.1354/vp.43-4-401
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Lymphoid Organ Development in Immunodeficient Mutant Mice

Abstract: Development of the primary and secondary lymphoid organs is a tightly controlled process. These tissues are highly organized to maximize efficiency of the immune response. Spontaneous and targeted mutations in laboratory mice have led to better understanding of the molecular interactions and signaling pathways essential to the development and organization of lymphoid tissues, and the functional consequences of loss or disruption of the normal structures. On the basis of studies of mutations in mice and other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 139 publications
0
41
0
Order By: Relevance
“…However, the secondary lymphoid organ phenotype of our NIK KO/KO mice appears to recapitulate the phenotype observed in NF-kB2-deficient mice (17,46) and is also very similar to that observed in LTb-deficient mice (26,47,48). Deficiency of NIK and various NF-kB family members that mediate noncanonical NF-kB signaling leads to similar, but not completely identical, secondary lymphoid organ defects (55), and secondary lymphoid organ development is exquisitely sensitive to slight differences in lymphotoxin/LTbR signaling, as revealed by studies of mice deficient in NIK and various NF-kB family members, studies of mice deficient in the lymphotoxin subunits LTa and LTb and the lymphotoxin receptor LTbR (17,56,57), and studies of temporal blockade of LTbR signaling at different times in utero (24,58,59). Thus, the differences in secondary lymphoid organ phenotypes between our NIK KO/KO mice and NIK aly/aly mice, as well as the other NIK-deficient mouse strain, may arise from Upon acute deletion of NIK in adult mice using our conditional NIK KO allele, we observed the abrogation of noncanonical NF-kB signaling, as assessed by p52 production, and a resulting reduction in B cell numbers in lymph nodes and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…However, the secondary lymphoid organ phenotype of our NIK KO/KO mice appears to recapitulate the phenotype observed in NF-kB2-deficient mice (17,46) and is also very similar to that observed in LTb-deficient mice (26,47,48). Deficiency of NIK and various NF-kB family members that mediate noncanonical NF-kB signaling leads to similar, but not completely identical, secondary lymphoid organ defects (55), and secondary lymphoid organ development is exquisitely sensitive to slight differences in lymphotoxin/LTbR signaling, as revealed by studies of mice deficient in NIK and various NF-kB family members, studies of mice deficient in the lymphotoxin subunits LTa and LTb and the lymphotoxin receptor LTbR (17,56,57), and studies of temporal blockade of LTbR signaling at different times in utero (24,58,59). Thus, the differences in secondary lymphoid organ phenotypes between our NIK KO/KO mice and NIK aly/aly mice, as well as the other NIK-deficient mouse strain, may arise from Upon acute deletion of NIK in adult mice using our conditional NIK KO allele, we observed the abrogation of noncanonical NF-kB signaling, as assessed by p52 production, and a resulting reduction in B cell numbers in lymph nodes and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Activation and regulation of the adaptive immune response is commonly thought to be a secondary function of the lymphatics with fluid and macromolecule recovery and return to the blood vasculature being the primary function (1318). However, mice that lack an adaptive immune response have reduced or absent secondary lymphoid organs and therefore have an incomplete lymphatic system (21). This suggests that the primary function of the lymphatic system is to serve and support the adaptive immune system.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to mention that although here we have created one multiple mutation scenario, but one can also generate different conditions using our in-silico model by altering the logical states of different pathway components. a) CD27 and LTBR knock-out scenario: The costimulatory receptors CD27 and LTBR (influencing the NFKB pathway) are involved in increased T-cell proliferation (DeBarros et al 2011;Wang and Fu 2004), and the mutations of these molecules have Temporal protein expression pattern been implicated in different immune-deficient conditions (Seymour et al 2006;van Montfrans et al 2012). In this study, we have observed that CD27 and LTBR together are responsible for the regulation of cytokine production.…”
Section: (Ii) Effect Of Multiple Mutations On Interleukin Productionmentioning
confidence: 85%